Dinamika Hukum Pemilihan Kepala Daerah Tahun 2024 Dalam Mewujudkan Demokrasi - Pranyoto, Agung Dwi (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
All provinces, cities, and regencies held simultaneous regional head elections in 2024, Indonesian democracy reached a milestone. This study examines the legal dynamics, administrative challenges, and issues that arise in simultaneous regional elections, particularly in the postponement of regional heads' terms, official appointments, and Constitutional Court election result disputes. This is normative legal research using statutory, conceptual, and comparative methods. The analysis found that the Constitutional Court granted 26 of 309 election result disputes, 24 of which resulted in a revote. Revote is a remedial method to ensure electoral equity and election results. These findings underline the significance of strengthening regulations, improving organizer professionalism, oversight, and public political literacy for democratic, fair, and accountable regional elections.